El cambio climático y nuestra salud: una emergencia desatendida - Salmón Mulanovich, Gabriela (2022)
The last report from the Intergovernmental Panel on Climate Change (IPCC) shows the limited margin we have to adapt to rising global temperature. The last four decades have been the warmest. Peru has been identified as a very vulnerable territory to the effects of climate change. The South American nation has experienced higher temperatures and retrenching glaciers, extreme climatic events, sliding crop yields, pests, floods in the Amazon basin and losses in its marine ecosystem. In addition, persistent inequity in Peru translates into uneven impacts, especially on populations that depend on natural resources for their livelihoods and are most susceptible to such adverse events. The negative effects on health can be direct due to extreme heat, or indirect due to increased exposure to forest fires, the migration of populations resulting from these events, or the transmission of certain diseases. This translates into identifying climate change as an ecosyndemic, which makes it possible to focus on common social and environmental drivers to simultaneously address several problems. Interventions in the urban environment that mitigate the impact of climate change on health and improve well-being are diverse. Decarbonizing the urban energy network has effects on air pollution and the emission of particulate matter, positively influencing health and reducing premature deaths. Considering the vulnerable situation of the territory, it is essential to incorporate these strategies with the most susceptible populations in mind, such as children and adolescents, who will continue to face climate change. After 18 months of COVID-19 health emergency, the country faces many challenges. The health crisis has taught Peru many lessons, but the health of future generations depends on how much we have learned.